High‐Performance and High‐Stability all‐Polymer Photomultiplication‐Type Organic Photodiode Using an NDI‐Based Polymer Acceptor with Precisely Controlled Backbone Planarity. (28th June 2022) - Lee, Sangjun; Lee, Gyeong Seok; Kang, Mingyun; Ha, Yeon Hee; Kim, Yun‐Hi; Chung, Dae Sung
Abstract: It is shown that the performance and the operational stability of an all‐polymer photomultiplication‐type organic photodiode (PM‐OPD) can be significantly enhanced by realizing near‐ideal spatial isolation of polymer acceptor via a synthetic approach. A series of new naphthalenediimide‐based D–A polymer acceptors, PNDI–Ph, PNDI–Tol, and PNDI–Xy, with different degrees of backbone planarity are synthesized. By introducing benzene, toluene, and p–xylene as the donor units, increasing intramolecular torsional angle is expected. Thus, 2D grazing‐incidence X‐ray diffraction reveals the highest paracrystalline disorder in the PNDI–Xy thin film. Furthermore, PNDI–Xy has the lowest surface energy resulting in the smallest surface energy difference with matrix donor polymer, poly(3‐hexylthiophene‐diyl) (P3HT). When combined with P3HT, the less aggregated and low surface energy nature of PNDI–Xy results in near‐ideal spatial isolation. Consequently, the all‐polymer PM‐OPD yielded a high external quantum efficiency of 770 000% with specific detectivity of 3.06 × 10 13 Jones. The physics behind the success of PNDI–Xy in PM‐OPD is discussed in conjunction with temperature‐dependent current density‐voltage analyses and drift‐diffusion simulations. Furthermore, the use of polymer acceptor enables the resulting PM‐OPD to retain its performance for 24 h, with significantly improved operational stability. Abstract : A synthetic strategy to realize near‐ideal spatial isolation of polymer acceptors for high‐performance all‐polymer photomultiplication‐type organic photodiode is suggested. By controlling the backbone planarity of polymer acceptor, an optimized all‐polymer photomultiplication‐type organic photodiode with external quantum efficiency > 700 000% and enhanced operational stability originating from the morphological robustness of all‐polymer bulk heterojunction are reported.